Analysis of factors affecting car purchasing decision - Bagus Randhyartha Gumilar; Ujang Sumarwan; Bagus Sartono (Faculty of Economics and Business Mulawarman University, 2020)
The sales of Mitsubishi Xpander have successfully penetrated the Low MPV car market after 13 years won by its competitors in first-year sales of 2017. The purpose of this study is to analyze the characteristics of Mitsubishi Xpander consumers, the effects of the marketing mix and brand awareness on purchasing decisions, and strategies to increase purchasing decisions. Primary data were obtained from 300 respondents who had bought a Mitsubishi Xpander. Furthermore, the data were analyzed by using the SEM method. The results show the price, product, and location positively and significantly influenced purchasing decisions. Promotion and brand awareness variables have positive but not significant influences on purchasing decisions. The company needs to evaluate the price range of the product, maintain quality, and increase dealer location points on Google Maps. In addition, companies can conduct promotional and branding activities adjusted to the middle-class consumer segment.